PERBANDINGAN ANALISIS BUKU TEKS PEMBELAJARAN SEJARAH SMA KELAS XI SEMESTER 1 TERBITAN ERLANGGA DAN YUDISTIRA. - Sari, Adilha Purnama; Husnita, Liza; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
In the process of learning one component that greatly affect the success of educational textbooks . Textbooks Textbooks are books that are written to handle students in accordance with the main points of discussion in the outlines of instructional programs and regulations. This textbook is a major textbook in teaching and learning. Research methods used in the study is the Content Analisys which describes the relationship between the subject matter of history in high school history textbooks with Competency Standards ( SK ) and the Basic Competency ( KD ) which exist on the Content Standards book danYudisthira grants . The results showed that the standard analysis of high competence and basic competence consists of two materials . Two such materials are science concepts and historical events . Based on the analysis of both high school history textbooks which grants and Yudisthira if ditinjaua in terms of suitability and completeness of the materials with the target presentation materials on the basis of competence , it grants a book better than the book Yudisthira so there is still a text book that has not met the target to be achieved ie the process of change , but the reality of the books now do not correspond to the learning objectives of factors , Content Standards , Level of student progress and teacher conditions. The conclusion of this study is that high school history text books of class XI on the basis of competence that analyze the development of life negarakerajaan Hindu - Buddhist state in Indonesia is targeting panyajian completeness of the material on the Basic Competence . But there is still a matter of history textbooks that have not lengkap.oleh because it prior to using the textbook teachers should analyze first whether it has been worth the textbook used or there are still shortcomings that need to be completed is by making teaching materials